Atividades de inglês mediadas pelo computador: um caminho para o letramento digital - Cortez, Cleide Diniz Coelho (2007)
This study aims to investigate what learning experiences were provided to a group of 6th grade high school students while attending an English course mediated by computer. The course aimed at developing reading skills from printed and digital comics and then developing a process of digital literacy. This research is based on a Vygotskyan (1934/2003) socio-interactive view of the process of learning and teaching underlined in the "Parâmetros Curriculares Nacionais" (PCN-LE Brasil, 1988b), which recommend the inclusion of technological resources in the learning and teaching process (PCN-Introdução, Brasil, 1988a). It is also based in the rescue of the literacy and digital literacy concepts (Freire, 1967/2002, 1970/2001; Sampaio & Leite, 2000; Soares, 2001, 2003; Kleiman, 2002; Almeida, 2005, among others). As for the methodology the present research is a case study which was conducted in a public school in São Paulo, involving 8 students and the teacher researcher. The results confirm that an English course mediated by computer is a feasible way of teaching and learning a foreign language and it can bring not only technological but also linguistic learning benefits